1995
DOI: 10.1007/bf01874873
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of chemical control of leek rust, a simulation study

Abstract: A model is presented which simulates chemical control against leek rust under a system of supervised control. The spread of disease between fields in one farm and the influx of spores from outside is part of the model. The possible reduction in fungicide sprays against leek rust following various preventive measures is estimated with this model. Results from this preliminary model suggest that supervised control of leek rust will result only in a considerable reduction in the number of fungicide sprays if the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…If only a certain percentage of rust spots in a certain area are detected, it is enough indication to have to apply fungicides in that area of the field because it is likely the wider area is also infected. Moreover, the economic threshold for leek rust disease is zero, meaning fungicides are to be applied whether one or fifty rust pustules are present [12]. In the context of reducing fungicide usage, it is therefore more important that rust pustules detected are effectively rust, and not a false positive, than to detect every rust pustule present, with the risk of increasing the amount of false positives.…”
Section: Preprocessing and Model Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…If only a certain percentage of rust spots in a certain area are detected, it is enough indication to have to apply fungicides in that area of the field because it is likely the wider area is also infected. Moreover, the economic threshold for leek rust disease is zero, meaning fungicides are to be applied whether one or fifty rust pustules are present [12]. In the context of reducing fungicide usage, it is therefore more important that rust pustules detected are effectively rust, and not a false positive, than to detect every rust pustule present, with the risk of increasing the amount of false positives.…”
Section: Preprocessing and Model Selectionmentioning
confidence: 99%
“…Moreover, constant full-field application of a small range of fungicides can have detrimental effects due to the build-up of fungicide resistance in the pathogen population [10]. It has further been shown that rust disease inoculum mainly stems from existing leek infection sites, with only minor significance of alternate hosts and survival spores [12]. This means that despite regular fungicide treatments, there is still a self-propagating presence of rust disease in leek growing areas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When this is not the case and a large epidemiological research investment is needed first, the increased efficiency of our approach is in the application of the first step, assessment of response of decision rules to weather. While our methodology was tailored to a weather-based warning system, similar approaches have been developed and applied for warning systems relying on field monitoring of diseases (de Jong, 1995;de Jong et al, 1995) or animal pests (van der Werfetal., 1996).…”
Section: Bowas Versionmentioning
confidence: 99%